Potentials in Udeskole: Inquiry-Based Teaching Outside the Classroom - Barfod, Karen S.; Daugbjerg, Peer (Frontiers in Education, 2018)
Most research on outdoor education, including the Scandinavian concept udeskole (regular curriculum-based teaching outside the classroom), has focused on pupils’ outcomes, whereas less has focused on teachers’ practices. In this article, we described the occurrence of inquiry-based teaching in udeskole. To analyze practice, we extended the notion of inquiry-based education. Within science and mathematics education, a strong stepwise teaching approach formerly was established, called Inquiry Based Science and Mathematics Education (IBSME), emphasizing pupils’ hypothesis testing, data validation and systematic experimentation. In this study, we broadened the IBSME-concept of inquiry in order to include a more holistic, non-linear teaching approach, but excluding teacher-instructed inquiry. Using this idea, we observed and documented by field notes how five experienced teachers practiced mathematics and science teaching in udeskole at primary level in Denmark. 28 outdoor days were observed. Each day was divided into separate teaching incidents with a distinct start and end. The level of teacher interference and possible choices in each teaching incidents formed the analytic background. We analyzed each of the 71 teaching incidents, and categorized each of them into one of five categories numbered 4-0. The categories designated numbers 4-2 contained the inquiry-based teaching incidents, and the categories designated 1 and 0 were categorized as ‘non-inquiry-based’. They contained teaching incidents where the teacher was instructing the pupils (category 1), and outdoor teaching activities with no sign of inquiry, called training activities (category 0). Our results showed that about half of the analyzed outdoor teaching practice seemed to be inquiry-based, emphasizing pupils’ choice and presenting cognitive challenge. This indicates that the analyzed udeskole had the potential to support an explorative and multifaceted inquiry-based teaching in mathematics and science, paving the way for a child-activating education. These results, albeit limited by the small number of observed teachers, supports the theoretical notion that udeskole is a potential way to strengthen pupils’ approach to inquiry.